The Marginalization of Food Safety Issues: An Interpretative Approach to Mass Media Coverage - Toby A. Ten Eyck (Journal of Applied Communications, 2000)
As the distance between lay consumers and food producers and processors increases, the mass media become more important in conveying information about food safety to the general public. This study shows how food safety issues have been marginalized by reporters, as coverage tends to cluster around crisis situations. Data were collected from articles indexed in the Readers’ Guide to Periodicals for the twelve years, 1986-1997. In addition to the quantitative analyses, coverage within the most popular magazines of two issues—mad cow disease and Alar—are examined. It is argued that food safety issues are not only marginalized, but are removed from consumer arenas into technical arenas.